Optimizing Fluorescein Isothiocyanate Dextran Measurement As a Biomarker in a 24-h Feed Restriction Model to Induce Gut Permeability in Broiler Chickens - Baxter, Mikayla F. A.; Merino-Guzman, Ruben; Latorre, Juan D.; Mahaffey, Brittany D.; Yang, Yichao; Teague, Kyle D.; Graham, Lucas E.; Wolfenden, Amanda D.; Hernandez-Velasco, Xochitl; Bielke, Lisa R.; Hargis, Billy M.; Tellez, Guillermo (Frontiers in Veterinary Science, 2017)
Fluorescein isothiocyanate dextran (FITC-d) is a 3–5 kDa marker used to measure tight junction permeability. We have previously shown that intestinal barrier function can be adversely affected by stress, poorly digested diets, or feed restriction (FR), resulting in increased intestinal inflammation-associated permeability. However, further optimization adjustments of the current FITC-d methodology are possible to enhance precision and efficacy of results in future. The objective of the present study was to optimize our current model to obtain a larger difference between control and treated groups, by optimizing the FITC-d measurement as a biomarker in a 24-h FR model to induce gut permeability in broiler chickens. One in vitro and four in vivo independent experiments were conducted. The results of the present study suggest that by increasing the dose of FITC-d (8.32 versus 4.16 mg/kg); shortening the collection time of blood samples (1 versus 2.5 h); using a pool of non-FITC-d serum as a blank, compared to previously used PBS; adding a standard curve to set a limit of detection and modifying the software’s optimal sensitivity value, it was possible to obtain more consistent and reliable results.